URBAN SEWERAGE PLANNING THROUGH COMMUNITY PARTICIPATION (Pakistan Journal of Science, 2022)
Planning for sewerage system is a difficult task and conflicts oftenly occur between decision makers and the community. This situation provides opportunities for community participation and the results thus appear in form of community decision-making. Concrete justifications are needed while designing sewerage system for the community. Therefore, there is a need to consider the public opinions while developing and executing sewerage related projects. In most of the Third World Countries, centralized decision making in form of top down approach is prevailing. Involvement of people in the decision-making process is rare and people seldomnly find an opportunity to raise their voices for their rights. In each society, the development trend varies and depends upon the type of communities and the governments. When a sewerage project is undertaken and communities are involved then rate of success for such projects increases. Because people think that their opinions are incorporated. Therefore, there is a need for participative development and then a forced top down or bottom up approach. Degree of people’s participation varies with respect to type of development project. It ranges from minimal involvement of people to complete decision making. This paper focuses on issues in sewerage planning particularly in urban areas and afterwards these can be replicated to larger areas. At the end, conclusions are made for practical implementation of future programs.
Keywords: Sewerage Problems; Community Participation; Developing Countries; Participatory Development